Speaking in Layers: The Role of Code-Mixing and Code-Switching in Multilingual Student Communities - Nisak, Winda Khoirun; Arini, Widiarini; Nadhiroh, Arfa'un (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2025)
The vast number of languages in the world enables individuals to master more than one language. Bilinguals and multilingual often blend the languages they know in daily interactions. This phenomenon, known as code-switching and code-mixing, reflects the dynamic nature of multilingual communication. Observations conducted at Universitas Nahdlatul Ulama Blitar involving multilingual teachers and students revealed distinct patterns: code-switching frequently occurs due to changes in conversational contexts or topics while code-mixing stems from habitual practices developed during first language acquisition. This study provides valuable insights into the linguistic behaviours of multilingual speakers and the factors influencing their language use.